DETERMINANTS OF SYARI'AH BASED FINANCING AND ITS CONTRIBUTION FOR SMEs DEVELOPMENT - Akhmad Sakhowi; Chalimah Chalimah (Universitas Airlangga, 2016)
This study examines the factors that affect the volume of Shariah-based financing for results and its contribution to the SMEs development in Indonesia. The determinant of sharia-based financing covers, third party funds, financing problems (non-performing Finance), inflation rates, interest rates on working capital loans, investment credit interest rate, and the gross domestic product. This study uses secondary data sourced from Indonesian Banking statistics published by Bank Indonesia with the observation period between 2007-2014. The analytical method used is descriptive and multiple regression. The results showed that the Gross Domestic Product, Third Party Funds and investment credit interest rates positive and significant impact on the volume of sharing based financing. The development of Shariah banking financing in the development of SMEs in Indonesia during 2007-2014 has increased fluctuate, but generally still has significant prospects. Shari'ah banking financing contribution in the SMEs development is needed because there are still many SMEs which have not obtained financing facility. Keywords: Shari’ah financing, Shari'ah commercial banks, Micro small and medium enterprises (SMEs)